Are strategies for success different in test cricket and one-day internationals? Evidence from England-Australia rivalry - Lohawala, N.; Rahman, M. A. (Journal of Sports Analytics, 2018)
The paper utilizes the entire cricketing data between England and Australia-Test and one-day international (ODI) matches played between 1877-2015 and 1971-2015, respectively-to provide an econometric perspective on the England-Australia rivalry. We employ the production function approach of Schofield (1988) and model Test match outcomes (loss, draw or win) using an ordinal probit model and ODI outcomes (loss or win) using a binary probit model. The results show that input measures critical to winning are different for the two formats and consequently a team should adopt different strategies in Test and ODI matches. We further show that influences which are perceived as important to match outcomes, including electing to bat first after winning the toss and effect of weather conditions, do not have any statistical support. However, there is strong evidence that England is at a disadvantage while playing a Test match in Australia. Besides, we find that home bias as typically defined in the literature may not necessarily indicate favoritism by umpires. The estimated models fit well and correctly predict about 70% of Test match outcomes and 95% of ODI outcomes.